In-situ preparation of yeast-supported Fe0@Fe2O3 as peroxymonosulfate activator for enhanced degradation of tetracycline hydrochloride. (May 2023) - Li, Bin; Li, Chen-Xuan; Wang, Yan; Xu, Weiyi; Cui, Kangping; Zhan, Xinyuan; Deng, Rui; Zhang, Xing
Abstract: Nano zero-valent iron (nZVI) is extensively used as a peroxymonosulfate (PMS) activator but suffers from the ease of oxidation and agglomeration due to its high surface energy and inherent magnetism. Here, green and sustainable yeast was selected as a support material to firstly in-situ prepare yeast-supported Fe 0 @Fe2 O3 and used for activating PMS to degrade tetracycline hydrochloride (TCH), one of the common antibiotics. Due to the anti-oxidation ability of the Fe2 O3 shell and the support effect of yeast, the prepared Fe 0 @Fe2 O3 /YC exhibited a superior catalytic activity for the removal of TCH as well as some other typical refractory contaminants. The chemical quenching experiments and EPR results demonstrated SO4 − was the main reactive oxygen species while O2 −, 1 O2 and OH played a minor role. Importantly, the crucial role of the Fe 2+ /Fe 3+ cycle promoted by the Fe 0 core and surface iron hydroxyl species in PMS activation was elucidated in detail. The TCH degradation pathways were proposed by LC-MS and density functional theory (DFT) calculation. In addition, the outstanding magnetic separation property, anti-oxidation ability, and high environmental resistance of the catalyst were demonstrated. Our work may inspire the development of green, efficient, and robust nZVI-based materials for wastewater treatment. Graphical abstract: Image 1 Highlights: Yeast-supported Fe 0 @Fe2 O3 was firstly prepared and used for peroxymonosulfate (PMS) activation and tetracycline hydrochloride (TCH) degradation. SO4 . − was the main reactive oxygen species while O2 −, 1 O2 and OH played a minor role. The crucial role of the Fe 2+ /Fe 3+ cycle promoted by Fe 0 core and surface iron hydroxyl species in PMS activation was elucidated in detail. The outstanding magnetic separation property, anti-oxidation ability and high environmental resistance of the catalyst were also demonstrated.